(untitled) (Indonesian Journal of Agrarian Law, 2026)
This study aims to analyze the effectiveness of agrarian reform implementation through the land access restructuring program in Karangtengah Village, Sukoharjo Regency, and to identify the factors influencing the success of its implementation. This study employs a qualitative method with a socio-legal approach to examine the gap between legal norms and empirical realities in the implementation of agrarian reform. Primary data was obtained through an interview with Aditya Dwi Prasetyawan, S.Ikom., serving as the First-Level Community Empowerment Officer in the Land Management and Empowerment Section of the Sukoharjo Regency Land Office. Secondary data was obtained through document analysis, specifically the 2024 Social Mapping Report on Agrarian Reform Access (ARA) Activities and various regulations related to agrarian reform. The research findings indicate that asset management through land certification has successfully enhanced legal certainty regarding community- d land; however, the effectiveness of access management in improving community economic well-being remains suboptimal. Major constraints include limited access to capital, technology, and markets, as well as weak coordination between the Sukoharjo Regency Land Office, the Sukoharjo Regency Government, and economic support institutions. Additionally, the distribution of assistance programs remains insufficiently inclusive and equitable. From a socio-legal perspective, this situation indicates a gap between the normative goals of agrarian reform and its implementation on the ground. Therefore, a more integrative, participatory, and sustainable agrarian reform policy model is needed so that agrarian reform not only results in the legalization of assets but also achieves social justice and improves community welfare.